Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan - Adinda Khansa Khairunnisa; Tri Murwaningsih (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
This research aims to: (1) determine the influence of work motivation on job satisfaction among employees of PT. Adhi Karya (Persero) Tbk., Tol Probowangi Project Package 1, (2) investigate the impact of work environment on job satisfaction among employees of PT. Adhi Karya (Persero) Tbk., Tol Probowangi Project Package 1, and (3) assess the combined effect of work motivation and work environment on job satisfaction at PT. Adhi Karya (Persero) Tbk., Tol Probowangi Project Package 1. The study utilizes a quantitative method with a descriptive analysis approach. Simple random sampling is employed for sample selection. Data collection is conducted through distribution of research questionnaires. The research findings indicate that: (1) work motivation has a positive and significant influence on job satisfaction among employees of PT. Adhi Karya (Persero) Tbk., Tol Probowangi Project Package 1, evidenced by t-value > t-table (2.108 > 1.99) and significance level 0.039 < 0.05, (2) work environment has a positive and significant influence on job satisfaction among employees of PT. Adhi Karya (Persero) Tbk., Tol Probowangi Project Package 1, evidenced by t-value > t-table (2.757 > 1.99) and significance level 0.007 < 0.05, and (3) it is found that there is a positive and significant impact from the combination of work motivation and work environment on job satisfaction among employees of PT. Adhi Karya (Persero) Tbk., Tol Probowangi Project Package 1, as indicated by F-value > F-table (6.898 > 3.12).